Factors affecting tourist satisfaction in ecotourism: A case study of the Phong Nha-Ke Bang National Park, Vietnam - Le, Anh Toai; Butowski, Leszek; Quirini-Popławski, Łukasz; Nguyen, Hoang Son (Quaestiones Geographicae, 2025)
The Phong Nha-Ke Bang National Park (PNKBNP) is one of the leading ecotourism destinations in Vietnam. To ensure sustainable development, understanding the factors influencing tourist satisfaction is crucial. This study surveyed 185 tourists using questionnaires to assess the significant factors affecting tourist satisfaction at the PNKBNP. The questionnaire responses were coded and analysed using Cronbach’s alpha reliability coefficient, exploratory factor analysis and regression analysis through the SPSS (Statistical Package for Social Sciences) 26.0 software. The study results revealed that tourist satisfaction is primarily dependent on five main factors: (1) destination attraction, (2) ecotourism services, (3) staff quality, (4) price, and (5) infrastructure. Among these, ‘destination attraction’ and ‘ecotourism services’ had the most significant impact on tourist satisfaction at the PNKBNP. This study also found that ‘staff quality’ had the least impact on tourist satisfaction. These findings provide a scientific basis for improving staff quality and enhancing tourist satisfaction at the Phong Nha-Ke Bang, while contributing to the sustainable development of ecotourism in Vietnam.